Nicholas Mystikos, patriarch of Constantinople in the light of his letters to Simeon, ruler of Bulgaria - Leszka, Mirosław J. (Balcanica Posnaniensia. Acta et studia, 2011)
The article analyzes the correspondence between Nicholas Mystikos, patriarch of Constantinople, and Symeon, ruler of Bulgaria, conducted between 912 and 925. The author examines the role of the patriarch as a political and religious mediator during the Byzantine-Bulgarian conflicts. The aim of the article is to present the attitude of Nicholas Mystikos toward the war with Bulgaria and to analyze the arguments employed in his letters to Symeon. The author applies the method of source analysis, relying primarily on the surviving letters of the patriarch. The study demonstrates that Nicholas Mystikos acted simultaneously as a spiritual authority, politician, and defender of the interests of the empire, while his letters combined religious and political argumentation. The patriarch emphasized the Christian community shared by Byzantines and Bulgarians, referred to the idea of Byzantium’s spiritual fatherhood over Bulgaria, and sought to persuade Symeon to conclude peace. The results of the analysis indicate that Nicholas’s correspondence constitutes valuable evidence of Byzantine political culture and methods of diplomacy in the tenth century.